CENTENARY OF ACADEMIC SPORTS BIOMECHANICS DISCIPLINE - Ivanova, G.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study. The sports biomechanics discipline coming to its birth centenary should undoubtedly be protected for its great service and benefits for humanity, and this is the core idea of our article. Results and conclusion. As things now stand, it is very likely that Biomechanics PhD dissertations will no more be defended since 2021 – that may be interpreted as indicative of the interest in the discipline being lost by the Russian research community. It is necessary to understand the true reasons for collapse of the academic biomechanics discipline on the verge of its birth centenary, otherwise our sports research may be stalled due to the need for a human movement theory to facilitate competitive progresses in many sports disciplines, particularly the most difficult ones – including e.g. figure skating, artistic and rhythmic gymnastics with their unprecedentedly beautiful and complex elements and movement culture on the whole. This movement culture is akin to ballet in terms of the movement expression and artistic merits – that have always been of special interest for the Russian biomechanics researchers working in collaboration with the leading choreographers and athletes in the above-mentioned and other projects by the Research Institute of Physical Education.